Pentecostalismo e arte: uma análise no contexto brasileiro - Souza, Mateus Lima de (2014)
The work analyzes the use of art in Brazilian Pentecostalism, dealing specifically with the visual arts and architecture, considering this use in worship spaces and in religious education. One begins with the idea that the relation of the Pentecostal faith with the arts is predominantly marked by rejection, revealing a preference for iconoclasm, therefore one seeks to understand the motives for such a rejection and what space and role this same art encounters in the bosom of Pentecostal religiosity. At the same time it is believed that the use of iconography in religious education is an exception to the iconoclastic posture. The first part of the work studied the development of Christian iconographic art and the main movements of iconoclasty in the Byzantine Empire and from the Protestant Reformation. The second part outlines a history of Brazilian Pentecostalism, from its origins in foreign lands, telling of the emergence and implantation of the main Pentecostal denominations of the country, outlining their profiles, as well as listing a serious of characteristics shared by the majority of the groups of the segment in question. The third part occupies itself with the main goal of the work, discussing the relation of Pentecostalism with the arts, focusing, at first, on the worship spaces. For this it explains the historic evolution of the Christian temples, taking into account artistic and theological aspects, and presents observations of the same nature about Pentecostal temples. Some theological, socio-economic and historical motives are presented which hypothetically contributed to Pentecostalism adopting an iconoclastic posture, which, in its less radical version, excludes in its worship spaces certain artistic manifestations, such as sculptures, or those with certain themes, such as the reproduction of the human image. There is a discussion of the use of figurative art in the literature directed to religious education, where one does not see the same limitations detected in the case of the temples. The posture of Brazilian Pentecostalism suggests a break with the western religious artistic tradition, the inexistence of a sacred art that is characteristic of it and an iconoclasm restricted to the worship houses, since religious education opens itself to didactic applications of iconographic art.